What can corporate governance build in shipping companies?. (1st January 2013) - Tuan, Luu Trong
This empirical inquiry into shipping companies in Vietnam seeks to discern whether corporate governance influences organisational culture and leadership, which in turn influences upward influence behaviour. Structural equation modeling (SEM) was utilised for the analysis of 418 responses returned from self-administered structured questionnaires sent to 710 middle level managers. From the findings emerged the linkage pattern of strong corporate governance and its organisational outcomes such as adhocracy, market, and clan cultures or transformational leadership. Adhocracy, market, and clan cultures and transformational leadership were also found to cultivate organisationally beneficial upward influence strategies.